Valley charge-transfer insulator in twisted double bilayer WSe2 - LingNan Wei; Qingxin Li; Majeed Ur Rehman; Yangchen He; Dongdong An; Shiwei Li; Kenji Watanabe; Takashi Taniguchi; Martin Claassen; Kostya S. Novoselov; Dante M. Kennes; Angel Rubio; et al. (Nature Communications)
Abstract In flat-band systems, emergent physics can be substantially modified by the presence of another nearby electronic band. For example, a Mott˘Hubbard insulator can turn into a charge transfer insulator if other electronic states enter between the upper and lower Hubbard bands. Here, we introduce twisted double bilayer (TDB) WSe2, with twist angles near 60°, as a controllable platform in which the K-valley band can be tuned to close vicinity of the Γ-valley moiré flat band. At half-filling, correlations split the Γ-valley flat band into upper and lower Hubbard bands and a charge-transfer insulator forms between the Γ-valley upper Hubbard band and K-valley band. Using gate control, we continuously move the K-valley band across the Γ-valley Hubbard bands, and observe a tunable charge-transfer insulator gap and subsequently a continuous phase transition to a metal. The tuning of Mott˘Hubbard to charge-transfer insulator establishes valley degree of freedom as a suitable knob for transitions between exotic correlated phases.